The Influence of Exchange Rate Analysis, TCPI and Tax Refund Policy Toward Foreign Tourist in Indonesia - Rif’atin Nabilah (Economics Development Analysis Journal, 2016)
Tourism is one of sector that have an important effect in economy of Indonesia, one of them as a source of foreign exchange earnings. That’s not caused due to the growth of Indonesian tourism that has a positive impact to foreign exchange earnings in Indonesia. The number of tourists in Indonesia is the factor that directly affects the foreign exchange earnings. This study aims to determine how much kurs, TCPI and Tax Refund as a macro economic variables to the number of Singapore tourists in Indonesia at 2009-2013. Analysis metode used in this study is OLS (Ordinary Least Square) using E-views program assistance. Research show that kurs and Tax Refund affects significantly to the number of Singapore tourists in Indonesia and TCPI didn’t make it. The number of tourists can be improved by efforts of Indonesia’s government in maximizing the policy implementation of Tax Refund, control the inflation in Indonesia and make rupiah doesn’t continously depreciate. With that efforts, more foreign tourists will come to Indonesia.